KEMELIMPAHAN VEGETASI LANTAI DAN TANAMAN BUDIDAYA DI EKOSISTEM KARST GUNUNGKIDUL, YOGYAKARTA - , DIAN PERAYANTI SINAGA; , Dr. Tjut Sugandawaty Djohan, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Floor vegetation and plants that grow in the ecosystem of karst in Gunungkidul depend greatly to the rainfall. The ecosystem of karst Gunungkidul has a very thin soil sphere and it is poor of hara. This study was conducted in the ecosystem of karst in the village of Banaran with the flat topography and in the village of Saptosari with the slope topography. This study aimed to learn the abundance of floor vegetation and the productivity of cultivated plants to the seasons in the ecosystem of karst in Gunung Kidul, Yogyakarta. Data of vegetation was collected by using the method of plot quadrate, using the measures of 10m x 20m, 5m x 5m, and 1m x 1m and it was repeated five times, and the measures would depend to the density of kind of presented things. The measured parameters were the kind of vegetation, density, soil texture, hara content with the measured parameters of NO3, NH4, PO4, Ca, C-organic, K, light intensity, air temperature, soil temperature, air humidity, and pH of soil. In the village of Banaran and Saptosari, there were 2 stations of study location respectively. The study results showed that in both study locations, the abundance of floor vegetations were growthform, bushes of Ageratum conyzoides, 15876 and Eupatorium odoratum 15792 individually per 0.1 ha, and growthform, grass of Imperata cylindrica 358, 844, 738 individually per 0.1 ha. Whereas the plentiful cultivated plants were Manihot utilissima, they were 200, 128, 6208 individually per 0.1 ha, and Arachis hypogaea, 15603 individually per 0.1 ha. The overabundance of natural vegetation did not depend to the canopy closing. It was because of location with any canopy, it would make the light intensity appropriate with the growth of bushes and grass. Thus, the abundance of cultivated plants greatly depend to the closing of canopy and topography.